2012
DOI: 10.1007/s11524-011-9664-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Femoral Injection among Seattle-Area Injection Drug Users

Abstract: Injection drug use (IDU) into central veins, most common among long-term IDUs with no other options, can lead to severe infectious, vascular, and traumatic medical consequences. To follow-up on anecdotal reports of femoral vein injection and related medical problems in Seattle, we analyzed data from the annual survey of a community-based syringe exchange program. A total of 276 (81%) of 343 program attendees completed the survey in August 2010. Among 248 IDUs, 66% were male, 78% white, and 86% primarily inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
14
1
1
Order By: Relevance
“…The extent of having ever injected subcutaneously or intramuscularly, either by intent or by accident, in our study was similar to the extent of ever injecting into the muscle found in Seattle, USA (Coffin, et al, 2012), but higher than that reported in an study in San Francisco, California (Binswanger, Kral, Bluthenthal, & Rybold, 2000). Subcutaneous and intramuscular injecting are likely to occur in other populations of people who inject drugs, particular among those populations were people have been injecting for long periods (Coffin, et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The extent of having ever injected subcutaneously or intramuscularly, either by intent or by accident, in our study was similar to the extent of ever injecting into the muscle found in Seattle, USA (Coffin, et al, 2012), but higher than that reported in an study in San Francisco, California (Binswanger, Kral, Bluthenthal, & Rybold, 2000). Subcutaneous and intramuscular injecting are likely to occur in other populations of people who inject drugs, particular among those populations were people have been injecting for long periods (Coffin, et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Subcutaneous and intramuscular injecting are likely to occur in other populations of people who inject drugs, particular among those populations were people have been injecting for long periods (Coffin, et al, 2012). Over time these practices, and their associated harms, may become an issue among the ageing cohorts of people who inject drugs that are found in many high income countries (European Monitoring Centre for Drugs and Drug Addiction, 2010), where people who have been injecting for long periods will be come more common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oltre alla compromissione del patrimonio venoso, sono note altre complicanze legate all'uso endovenoso di sostanze: ascessi, celluliti, trombosi, tromboflebite settica, fistole artero-venose e pseudo aneurismi. Mission 46............................................................................................................................................................................................................59 L'iniezione può inoltre esporre a infezioni locali o sistemiche (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Non è solo la pratica iniettiva a presentare dei rischi per la salute, ma anche altre tipologie di consumo che, accompagnandosi a comportamenti a rischio, possono ad esempio incrementare il rischio di contrarre infezioni sessualmente trasmesse, pertanto la valutazione clinica dovrebbe includere domande relative agli attuali modelli di uso di sostanze e comportamenti a rischio, al fine di mettere in atto interventi di educazione sanitaria per entrambe le tipologie di pazienti.…”
Section: Discussioneunclassified